2016
DOI: 10.1007/s10840-016-0214-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of uninterrupted rivaroxaban taken preoperatively for radiofrequency catheter ablation of atrial fibrillation compared to uninterrupted warfarin

Abstract: Uninterrupted rivaroxaban taken preoperatively for AF ablation is clinically effective and safe. Its ACE profile is similar to warfarin. ACT is sufficient for monitoring anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
2
15
2
Order By: Relevance
“…In concordance with our results, Lakkireddy et al demonstrated that uninterrupted rivaroxaban is as safe and efficacious in preventing bleeding and thromboembolic events in patients undergoing AF ablation as is uninterrupted warfarin therapy . Tao et al also confirmed our results in their prospective study clarifying the safety and efficacy of using uninterrupted morning rivaroxaban for anticoagulation during AF ablation, especially with regard to asymptomatic cerebral embolism and anticoagulation parameters . In addition, Kuwahara et al reported that apixaban 5 mg or 2.5 mg b.i.d.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In concordance with our results, Lakkireddy et al demonstrated that uninterrupted rivaroxaban is as safe and efficacious in preventing bleeding and thromboembolic events in patients undergoing AF ablation as is uninterrupted warfarin therapy . Tao et al also confirmed our results in their prospective study clarifying the safety and efficacy of using uninterrupted morning rivaroxaban for anticoagulation during AF ablation, especially with regard to asymptomatic cerebral embolism and anticoagulation parameters . In addition, Kuwahara et al reported that apixaban 5 mg or 2.5 mg b.i.d.…”
Section: Discussionsupporting
confidence: 92%
“…11 Tao et al also confirmed our results in their prospective study clarifying the safety and efficacy of using uninterrupted morning rivaroxaban for anticoagulation during AF ablation, especially with regard to asymptomatic cerebral embolism and anticoagulation parameters. 22 In addition, Kuwahara et al reported that apixaban 5 mg or 2.5 mg b.i.d. has similar safety and effectiveness to warfarin for the prevention of cerebral thromboembolism during the periprocedural period of AF ablation.…”
Section: Discussionmentioning
confidence: 99%
“…For all other studies, major bleeding was defined as that severe enough to require blood transfusion, surgery, or pericardial drainage. 12,17,18,[20][21][22] In the COMPARE study 7 of continuous vs interrupted warfarin, major bleeding was defined more broadly as cardiac tampo-nade, hematoma requiring intervention, massive hemoptysis, hemothorax, retroperitoneal bleeding, need for transfusion, or bleeding causing symptoms. As reported in Table 1, follow-up for bleeding end points ranged from inhospital to as much as 90 days.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…More recently, numerous studies were published, including additional randomized data that may strengthen the power of pooled outcomes. [10][11][12][13] Therefore, we aimed to perform an updated systematic review and meta-analysis to investigate the efficacy and safety of NOACs vs VKAs for uninterrupted OAC in patients with AF undergoing catheter ablation.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 2694 records were identified, of which 29 studies met the predefined criteria and hence were included in the analysis. The detailed search flowchart was illustrated in Figure .…”
Section: Resultsmentioning
confidence: 99%